+0  
 
0
152
1
avatar

(x-2)^2/3=36

 Aug 8, 2019
 #1
avatar+106515 
+1

(x-2)^(2/3) =  36   raise  both sides to the  3/2   power

 

[ (x - 2) ^(2/3) ]^(3/2)   =  36 ^(3/2)

 

(x - 2)^(2/3 * 3/2)  =  ( √ [ 36] )^3

 

(x - 2) ^1   =  (6)^3

 

x - 2 =  216     add 2 to  both sides

 

x   = 218

 

Check

 

(218 - 2)^(2/3)   =36   ???

 

(216)^(2/3)  = 36  ???

 

[ (216)^(1/3) ] ^2  = 36  ???

 

[ ∛216] ^2  = 36  ???

 

[6]^2   = 36        true   !!!!

 

 

 

cool cool cool

 Aug 8, 2019
edited by CPhill  Aug 8, 2019

16 Online Users